Effect of rotational electrode on : the performance of EDM milling - Iqbal, Asif (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Electrical discharge machining (EDM) is a non- conventional machining process based on removing material from a workpiece by means of a series of electrical discharges (sparks) that develops a temperature of about 8,000°C to 12,000ºC between a tool electrode and workpiece in the presence of a dielectric fluid. Due to high temperature of the sparks, workpiece is melted and vaporized, at the same time the electrode material is also eroded by melting and vaporization. The performance of EDM process is measured by material removal rate, electrode wear ratio and surface roughness. Surface roughness is a significant design factor that has a considerable influence on properties such as fatigue, strength and wears resistance. Electrode wear is one of the major problems in EDM process. Due to electrode wear (EW), electrodes loose their geometrical shape resulting in inaccuracy of the cavity formed in the workpiece during EDM. In this regard, it becomes imperative to reduce EW and improve Ra in EDM. Selection of appropriate machining parameters and their optimum value is one of the most important aspects for optimum utilization of EDM process. In this research, electrical discharge milling (ED-milling) is used to reduce electrode wear where a cylindrical tool electrode rotates and follows a programmed path in order to obtain the desired shape of a part. The use of standard electrodes in EDM milling eliminates the need for customized shaped electrodes. The combined effect of electrical and non electrical process parameters on EDM milling performance has been investigated in this research. Voltage (V), rotational speed of electrode (N) and feed rate (ƒ) are used as process parameters. Consequently, their influence on responses such as: MRR, EWR and surface integrity have been assessed. Stainless steel (AISI 304) and copper were used as the workpiece and electrode material respectively. 2-level factorial with Central Composite Design (CCD) of second order has been employed to carry out the investigation and developed prediction models of MRR, EWR and Ra. The effect of electrode rotation and the combination of process parameters on the micro crack, recast layer thickness and material migration on both workpiece and electrode were also examined. Ra was measured using Mitutoyo Surftest (SV-514) while MRR and EWR were calculated based on the volume of materials removed and machining time respectively. Scanning electron microscope/Energy dispersive x-ray (SEM/EDX) was used to asses the surface topography as well as migration on the EDMed surfaces. The highest value of MRR was observed at the combination of V 120V, N 1500 rpm and ƒ 6 ;m/s while the lowest value of EWR and Ra was found at the combination of V 100V, N 1250 rpm and ƒ 5 ;m/s; and V 80V, N 1500 rpm and ƒ 4 ;m/s respectively. Quadratic fitting model was developed for both MRR and EWR while linear fitting model was developed for Ra. The prediction models show that all three process parameters have significant effect on EDM performance. Electrode rotation improves the surface integrity of EDMed surface. The number of micro cracks, recast layer thickness and material migration reduces significantly when rotating electrode was used compared to that of stationary electrode. The combination of electrical and non electrical process parameters proved to be a useful method to improve the overall EDM performance.